Estimation of the Toxicity of Silver Nanoparticles by Using Planarian Flatworms. Issue 1 (March 2014) - Kustov, Leonid; Tiras, Kharlampii; Al-Abed, Souhail; Golovina, Natalia; Ananyan, Mikhail
The regeneration of planarian flatworms — specifically, changes to the area of the regeneration bud (blastema) after surgical dissection — was proposed for use as a robust tool for estimating the toxicity of silver nanoparticles. The use of Planaria species, due to their unique regenerative capacity, could result in a reduction in the use of more-traditional laboratory animals for toxicity testing. With our novel approach, silver nanoparticles were found to be moderately toxic to the planarian, Girardia tigrina .